exploring co.creation, for citizen participation and influence on public space - Björkman, Annsofi (My University, 2020)
Architecture is a physical manifestation of those who have the privilege to build. It therefore has the chance to rebalance social injustice. The end-user is often distanced from the design process and the developers often lack knowledge on the local social, cultural and environmental landscape. But what happens when an authoritarian process turns into an open and democratic one? What happens when we share the privilege to build? With a belief that sharing the privilege not only creates a greater understanding for the built environment, but also empowers people to act on that knowledge - the purpose of this thesis is to support a sustainable, democratic and just development of public spaces by investigating the possibilities of increased citizen engagement and influence. This thesis focuses on participatory processes. Concepts such as Tactical Urbanism, Placemaking and Common Governance are studied, as well as their application in practice. Common aspects are collaborative actions and the importance of citizen influence to support creative and positive social development. A case study conducted in Gothenburg City exemplifies the top-down administration of urban development in Sweden. By looking at different initiatives, structures, processes, working methods and tools applied in practice, an analysis of the level of citizen influence has been conducted and through this missing links have been found. Citizens influence is usually limited to input or consultation, it is rare to see citizens having a co.determine role. Civil servants are expressing a lack of political support and flexibility in structures, but also lack in communication, as well as individual interest and competence. Based on the case study and the theory a synthesized process model for co.creation has been developed. With the intention to be easy assimilated and accessible as support for implementation as a working model. Co.creation is more than a process, it is a mindset. Working with co.creation challenging the role of the profession. It requires new ways of thinking, change in attitudes and an openness to innovative working models and collaborations. And it raises a curiosity to find out what a society can become - if more people had the privilege to build.
Keywords: public spaces, participatory processes, urban development, citizen influence, co.creation